Kutya éji dala . Dog's Night Song - Bódy, Gábor (Schlett, István, 1983)
A disconcerting portrait of a Hungarian town thrown into disarray by the arrival of a new parish priest, the film is a web of fragmented and often intersecting narratives: the audience follows a wheelchair-bound veteran of the 1956 uprising unable to commit suicide; an astronomer who moonlights in a punk band; the abused wife of an explosives officer who runs away to join the band; and their son, who films his world with a German tourist's Super 8 camera. A pioneering work of European cinema.